Narrative Types in Our Arab Heritage - Naser Jaber (Shabaneh)‎ (My University, 2007)
This research aims studying the real relationship between modern narrative structures, with all their forms, and Arab tradition; it also aims at following some of those forms and comparing them with some modern narrative arts, like: story, play and biography; the study tries to offer an objective scientific view, as far as possible, out from the many diverse view points, the ardour of some which to tradition and its narrative forms set them far away from truth, while others underestimated this tradition and considered it as no more than a chanting one with no room for narrative in it.

يسعى هذا البحث إلى دراسة عدد من أنماط السرد في تراثنا العربي في سبيل إثبات الحقيقة السردية العربية، بالإضافة إلى دراسة حقيقة العلاقة بين البنى السردية بأشكالها المختلفة والتراث العربي، كما يسعى إلى تتبع بعض تلك الأشكال ومقاربتها ببعض فنون السرد الحديثة كالقصة والمسرحية والسّيرة. وتطمح هذه الدراسة إلى تقديم رأي علمي موضوعي-قدر المستطاع-في خضم آراء عديدة بعضها أخرجته حماسته للتراث وأشكاله السردية عن دائرة الحقيقة، وبعضها الآخر تنكّر للتراث حتى كاد يعدّه تراثاً غنائياً لا مكان للسرد فيه.
أنماط السّرد في تراثنا العربي